Antimicrobial activity of microcapsules with aqueous extract of chambá (Justicia pectoralis jacq) - Guimarães, Thays; Silva, Larissa; Lima, Carolline; Magalhães, Francisco Ernani; Figueiredo, Evânia Altina (Revista Ciência Agronômica, 2020)
To ensure the antimicrobial activity of the aqueous extract of chambá, it is essential to protect its bioactive compounds. The objective was to preserve its characteristics, aiming to provide the food industry with a natural antimicrobial. Three microcapsule formulations made with maltodextrin and cyclodextrin were developed, both including the aqueous extract of chambá leaves dried through lyophilization. The aqueous extract was initially submitted to in vivo toxicity analysis using zebrafish and the microcapsules were characterized through studies of morphology, hygroscopicity, water solubility, particle size, zeta potential, color determination, microencapsulation efficiency and antimicrobial activity. The aqueous extract of chambá was not considered to be toxic. The microcapsules had irregular shapes, with sizes varying from 0.58 to 1.15 μm. Solubility values ranged from 74.69 to 76.8% and hygroscopicity varied from 2.07 to 4.34%. Additionally, it obtained efficient encapsulation of the phenolic compounds, showing antimicrobial activity against Staphylococcus aureus, Listeria monocytogenes, Salmonella Enteritidis and Escherichia coli, with its use being an alternative as a natural antimicrobial agent.